Essays in Business Administration by a Street Smart Manager - Deshpande, Prabhakar (Digital Repository of Theses, 2024)
This thesis is inspired by the excellent book - What they don’t teach you at Harvard Business School (1984) by Mark McCormack. And there is a reason for that. The researcher has around 30 years of experience covering technology, strategy, marketing, journalism, social work and more. Hence, if the researcher is writing a thesis after 30 years of work experience, it is only natural that the thesis will include a greater proportion of street smart management ideas. A CEO can teach more management than a person who has just passed out of a Business School. However, this should not mean that Business School education is to be undermined or belittled. The researcher has a Master’s Diploma in Business Administration from Symbiosis Institute of Management Studies, which may not be a top rung business school, but is very respected and prestigious. The researcher also has an engineering degree from IIT Bombay, which is certainly no less an institution than MIT USA. What an engineering degree does is that it makes you focus on the essentials. Hence engineers are sometimes at loss for the roundabout wanderings of Liberal Arts students. Engineering is a very structured and linear academic discipline. Engineering stems from quantitative and analytical methodologies of thinking. However, Management does not function in a very structured and analytical manner. There is quite a bit of intuition, gut feel, and human element to management.